Ultrastructural evaluation of oocyte envelopes of zebrafish (Danio rerio) (Hamilton, 1822) after TiO2 nanoparticle exposure - Akbulut, Cansu; Kotil, Tuğba; Yön, Nazan Deniz (Archives of Biological Sciences, 2018)
Titanium dioxide (TiO2)is one of the most widely used nanoparticles, and aquatic organisms are especially exposed to it. To examine reproductive toxicology, zebrafish were exposed to different concentrations (1, 2 and 4 mg/L) of TiO2 nanoparticles. The ultrastructure of the theca cell, zona radiata structure and follicular epithelium were examined in detail by transmission electron microscopy (TEM). No abnormalities were observed in the control group; however, degeneration of pore and microvilli structures of the zona radiata, vacuolization in the ooplasm, mitochondrial swelling and mitotic catastrophe (the mechanism for eliminating mitosis-incompetent cells in eukaryotes) were detected in the exposure groups. These results indicate that TiO2 nanoparticle exposure causes paraptotic-type cell death in zebrafish oocytes, follicular and theca cells. In light of the observed histopathological changes, it was concluded that TiO2 exposure inhibited oogenesis and the reproductive capability in zebrafish. https://doi.org/10.2298/ABS170303035A Received: March 3, 2017; Revised: August 8, 2017; Accepted: September 20, 2017; Published online: October 3, 2017 How to cite this article: Akbulut C, Kotil T, Yön DN. Ultrastructural evaluation of oocyte envelopes of zebrafish (Danio Rerio) (Hamilton, 1822) after TiO2 nanoparticle exposure. Arch Biol Sci. 2018;70(1):159-65.